Antigenic properties of VP15 from white spot syndrome virus in kuruma shrimp Marsupenaeus japonicus. Issue 101 (June 2020) - Boonyakida, Jirayu; Xu, Jian; Satoh, Jun; Nakanishi, Takafumi; Mekata, Toru; Kato, Tatsuya; Park, Enoch Y.
Abstract: White spot syndrome virus (WSSV) is known as one of the most lethal pathogenic viruses in shrimp causing massive damage to shrimp aquaculture industries. To date, no effective treatment or prevention has been found. In this study, five recombinant viral proteins VP15, VP19, VP24, VP26, and VP28 were expressed and purified in E. coli, which were employed as candidates against WSSV in Kuruma shrimp Marsupenaeus japonicus . In vivo antiviral assay in this study newly revealed that VP15 of major nucleocapsid protein, being known as a DNA-binding protein provided the substantial protection against the viral infection when pre-injected into shrimps. Furthermore, we also verified the immunogenic effects of purified VP15 and VP19 proteins produced in a silkworm-bacmid expression system. Taken together, our study identified VP15 as an effective candidate against WSSV infection in the Kuruma shrimp. It is interesting to uncover why and how VP15 is involved in the immune memory in shrimp in the future study. Graphical abstract: Image 1 Highlights: White spot syndrome virus (WSSV) is one of the most lethal pathogens in shrimp. Viral proteins of WSSV were expressed and purified from both E. coli and silkworm. VP15 provided a protective effect against WSSV in Kuruma shrimp. VP15 is identified as a vaccine candidate against WSSV.